Pengaruh Harga, Suasana Toko, dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Vanko Coffee Surabaya (The Influence of Price, Store Atmosphere, and Service Quality on Purchasing Decisions at Vanko Coffee Surabaya) - Permana, Akbar Bintang; Nurhadi, Eko; Atasa, Dita (Jurnal Ilmiah Sosio Agribis, 2025)
The high level of consumption of Indonesian people regarding coffee consumption has made coffee shops spread throughout the region. This study aims to determine the effect of service quality, price and store atmosphere on purchasing decisions at Vanko Coffee Surabaya. The sample used was 100 respondents. The sampling method uses purposive sampling, namely by taking samples based on whoever happens to meet the researcher. This study uses Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS) as a statistical tool. Data collected with questionnaires that have been tested for validity and reliability. The results showed that: service quality has a positive and significant effect on purchasing decisions; price has a negative and insignificant effect on purchasing decisions; store atmosphere has a negative and insignificant effect on purchasing decisions.Keywords: Consumer characteristics, price, store atmosphere, service quality, purchasing decisions